2021
DOI: 10.1002/advs.202002831
|View full text |Cite
|
Sign up to set email alerts
|

PADI2‐Catalyzed MEK1 Citrullination Activates ERK1/2 and Promotes IGF2BP1‐Mediated SOX2 mRNA Stability in Endometrial Cancer

Abstract: Peptidylarginine deiminase II (PADI2) converts positively charged arginine residues to neutrally charged citrulline, and this activity has been associated with the onset and progression of multiple cancers. However, a role for PADI2 in endometrial cancer (EC) has not been previously explored. This study demonstrates that PADI2 is positively associated with EC proregression. Mechanistically, PADI2 interacting and catalyzing MEK1 citrullination at arginine 113/189 facilitates MEK1 on extracellular signal‐regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 74 publications
2
60
0
Order By: Relevance
“…Endometrial cancer (EC) is a common malignant gynecological tumor worldwide. Even in early-stage cancer, routine surgery has a great impact on the fertility of patients, and the development of effective interventions is of great importance [ 99 , 100 ]. Ma et al reported that m 6 A RNA methylation was closely associated with the clinicopathological stage and prognosis of endometrial cancer and that METTL14 was used as a potential marker for the diagnosis and prognosis of endometrial cancer [ 101 ].…”
Section: Introductionmentioning
confidence: 99%
“…Endometrial cancer (EC) is a common malignant gynecological tumor worldwide. Even in early-stage cancer, routine surgery has a great impact on the fertility of patients, and the development of effective interventions is of great importance [ 99 , 100 ]. Ma et al reported that m 6 A RNA methylation was closely associated with the clinicopathological stage and prognosis of endometrial cancer and that METTL14 was used as a potential marker for the diagnosis and prognosis of endometrial cancer [ 101 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among over 100 types of RNA modifications, m6A is the most prevalent one in modification of mRNA and non‐coding RNA 45 . Accumulating evidences indicate that m6A is involved in a series of physical and pathological processes, including embryonic stem cells development, tumorigenesis, spermatogonia differentiation, CNS myelination, heart failure and diabetes 46–54 . Recent studies revealed that demethylase FTO could control cell cycle progression and proliferation by targeting m6A modification of cyclin D1 mRNA 32 .…”
Section: Discussionmentioning
confidence: 99%
“… 45 Accumulating evidences indicate that m6A is involved in a series of physical and pathological processes, including embryonic stem cells development, tumorigenesis, spermatogonia differentiation, CNS myelination, heart failure and diabetes. 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 Recent studies revealed that demethylase FTO could control cell cycle progression and proliferation by targeting m6A modification of cyclin D1 mRNA. 32 What's more, expression of miRNA in cellular aging of HDFs and old PBMCs could be regulated by m6A‐dependent AGO2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…PADI2-catalyzed MEK1 R113/189 citrulline is a key factor in endometrial cancer. These findings suggest that targeting PADI2/MEK1 may be a potential therapy for endometrial cancer patients (91). The roles of different m 6 A regulators in regulating RNAs in endometrial cancer are shown in Figure 3 and Table 2.…”
Section: Function Of M 6 a On Mrna In Endometrial Cancermentioning
confidence: 90%